2021
DOI: 10.1007/s10856-021-06500-2
|View full text |Cite
|
Sign up to set email alerts
|

The corticospinal tract structure of collagen/silk fibroin scaffold implants using 3D printing promotes functional recovery after complete spinal cord transection in rats

Abstract: No effective treatment has been established for nerve dysfunction caused by spinal cord injury (SCI). Orderly axonal growth at the site of spinal cord transection and creation of an appropriate biological microenvironment are important for functional recovery. To axially guiding axonal growth, designing a collagen/silk fibroin scaffold fabricated with 3D printing technology (3D-C/SF) emulated the corticospinal tract. The normal collagen/silk fibroin scaffold with freeze-drying technology (C/SF) or 3D-C/SF scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 58 publications
0
7
0
2
Order By: Relevance
“…This could be because collagen introduced from tissue-engineered scaffolds substitutes the collagen fibers produced during wound healing and prevents the process of wound contraction, thereby minimizing scarring [136,137]. However, collagen has relatively poor mechanical characteristics, making it difficult for collagen-based scaffolds to retain stability during spinal cord repair, particularly when printed into a hollow or geometrically complex structure such as corticospinal tracts [138]. Furthermore, collagen experiences rapid in vivo biodegradation and may disappear within a few days after implantation, which is insufficient for longterm spinal cord repair.…”
Section: −Hydrophobicity −Slow Degradation Rate −Inhibits Cell Adhesionmentioning
confidence: 99%
“…This could be because collagen introduced from tissue-engineered scaffolds substitutes the collagen fibers produced during wound healing and prevents the process of wound contraction, thereby minimizing scarring [136,137]. However, collagen has relatively poor mechanical characteristics, making it difficult for collagen-based scaffolds to retain stability during spinal cord repair, particularly when printed into a hollow or geometrically complex structure such as corticospinal tracts [138]. Furthermore, collagen experiences rapid in vivo biodegradation and may disappear within a few days after implantation, which is insufficient for longterm spinal cord repair.…”
Section: −Hydrophobicity −Slow Degradation Rate −Inhibits Cell Adhesionmentioning
confidence: 99%
“…In another study, multichannel GelMA NGCs with different inner diameters were fabricated by DLP or projection-based 3D printing [119], and it was found that larger inner diameters are more conducive to the longitudinal migration of cells along the channels [54,120]. Differ from regular and uniform microchannels, Li et al [121] designed cryogenic 3D-printed collagen/silk fibroin implants with four irregular channels, the biomimetic internal microarchitecture of which precisely simulated the spatial microstructure of the spinal tracts, presenting fewer lesions and disordered structures of the injured spinal cords than those prepared by freeze-drying technology by HE analysis. By µCPP, Koffler et al [55] created a bionic scaffold with 20 µm-diameter microchannels loaded with NPCs and implanted in the disrupted spinal cord of rats.…”
Section: D-printed Functional Bioengineered Constructs With Topograph...mentioning
confidence: 99%
“…Fabrication of the exosomes loaded 3Dprinted collagen/silk fibroin scaffolds A 3D-Bioplotter ™ system (Regenovo, Hangzhou, China), including a personal computer, x-y-z motion nozzle and temperature controllers platform, was served for printing scaffolds. For biocompatibility and biodegradability, a blend of collagen and silk fibroin was prepared as the fabrication material as described previously (Jiang et al, 2021;Li et al, 2021;Chen et al, 2022). For collagen Liu et al, 2019;Jiang et al, 2020), we purchased fresh bovine tendons from a local slaughter house.…”
Section: Isolation and Characterization Of Mexos And Hypo-mexos Deriv...mentioning
confidence: 99%